Regulatory requirements of banks and arbitrage in the post-crisis federal funds market - Rod Garratt; Sofia Priazhkina (Bank of Canada, 2022)
This paper explains the nature of interest rates in the U.S. federal funds market after the 2007-09 financial crisis. We build a model of the over-the-counter lending market that incorporates new aspects of the financial system: abundance of liquidity, different regulatory standards for banks, and arbitrage opportunities created by limited access to the facility granting interest on excess reserves. The model determines the equilibrium federal funds rate as a function of the policy rates and explains the "leaky floor" phenomenon in which we observe federal funds rates that are strictly below the interest rate paid on reserves. Using the model, we explain the impact of raising government yields and tightening the Liquidity Coverage Ratio (LCR) and the Supplementary Leverage Ratio (SLR) requirements on the federal funds rates.
Keywords: E42; E58; G2; G28; 330; Central bank research; Economic models; Financial institutions; Financial markets; Financial stability; Wholesale funding; Financial system regulation and policies